Identifikasi Pola Penyebaran Pencemaran Air Tanah Berbasis Sistem Informasi Geografis - Rizdha Adzidzah Fadhilah; Ihsan Ihsan; Abdul Rachman Rasyid (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
Increased population growth follows changes in land use, resulting in a higher risk of groundwater pollution. Such conditions can affect groundwater pollution as a source of clean water. The purpose of this study was to identify patterns of distribution of groundwater pollution based on geographic information systems in Mariso District. Therefore, Mariso District is determined to be a research location to find out the spread of groundwater pollution. This aims to identify patterns of distribution of groundwater pollution based on geographic information systems in Mariso District. Data use d in this study are primary data from observation, while secondary data obtained through related regulation, literature, and previous research. The analysis was carried out through map overlay techniques in the Arcgis application of the predetermined variables. Several factors that are thought to influence groundwater quality include pollutant sources, the distance of pollutant sources with the location of wells which have an impact on the potential for diarrheal disease in the study site. The results showed that 26% of septic tanks <10 meters away from wells included Lette, Mattoanging, Bontorannu and Kunjungmae village. This has to do with the condition of the slums which are spread over several in Mariso Subdistrict. The pattern of pollution of ground water distribution that shows the red zone is the Bontorannu Village, Panambungan Village and Kunjungmae Village which have the potential to affect the surrounding villages.